CHANGES OF INDICATORS OF THE PERIPHERAL BLOOD AND HAEMOPOIESIS AT INKORPORATION OF THE DEPLETED URANIUM IN THE EXPERIMENT - D. V. Gerasimov; R. V. Afanasyev; O. Yu. Terezanov (Радиационная гигиена, 2015)
In article is considered the experiment with incorporation of the solution of the mixed oxides of the depleted uranium to laboratory animals (the rats) and following the cytological study of the peripheral blood and marrow after influence. The changes of indicators of the peripheral blood and haemopoiesis of experimental animals are indicative of the effort processes of indemnification, that shows depleted uranium’s radioactive and toxicological effects and insolvency of natural protective mechanisms of the organism. The results of the research have shown that changes of the haemopoiesis were ambiguous. There was shown the oppression myeloid haemopoiesis and leukopenia to the third month of the experiment. In same time existed the increase an erythroid parts of hemopoiesis. The parameters of the peripheral blood and haemopoiesis to completion of the experiment did not reach checking importances that points to practicability of the long observation for animal after one-shot influence with DU.